Improved interfacial quality of GaAs metal-oxide-semiconductor device with NH3-plasma treated yittrium-oxynitride as interfacial passivation layer. (January 2016) - Lu, H.H.; Xu, J.P.; Liu, L.; Wang, L.S.; Lai, P.T.; Tang, W.M.
Abstract: The interfacial and electrical properties of GaAs metal-oxide-semiconductor capacitors with yittrium-oxynitride interfacial passivation layer treated by N2 −/NH3 -plasma are investigated, showing that lower interface-state density (1.24 × 10 12 cm − 2 eV − 1 near midgap), smaller gate leakage current density (1.34 × 10 − 5 A/cm 2 at Vfb + 1 V), smaller capacitance equivalent thickness (1.43 nm), and larger equivalent dielectric constant (24.5) can be achieved for the sample with NH3 -plasma treatment than the samples with N2 −/no-plasma treatment. The mechanisms lie in the fact that NH3 -plasma can provide not only N atoms, but H atoms and NH radicals to effectively passivate the high-k/GaAs interface, thus less pinning the Femi level at high-k/GaAs interface. Highlights: Using yittrium-oxynitride as interfacial passivation layer to get a good interface Using NH3 or N2 plasma to treat YON interfacial passivation layer and passivate the interface The sample treated by NH3 plasma shows better performance.